Plasma Amyloid Is Associated with White Matter and Subcortical Alterations and Is Modulated by Age and Seasonal Rhythms in Mouse Lemur Primates - Gary, Charlotte; Hérard, Anne-Sophie; Hanss, Zoé; Dhenain, Marc (Frontiers in Aging Neuroscience, 2018)
Accumulation of amyloid-β (Aβ) peptides in the brain is a critical early event in the pathogenesis of Alzheimer's disease (AD), the most common age-related neurodegenerative disorder. There is increasing interest in measuring levels of plasma Aβ since this could help in diagnosis of brain pathology. However, the value of plasma Aβ in such a diagnosis is still controversial and factors modulating its levels are still poorly understood. The mouse lemur (Microcebus murinus) is a primate model of cerebral aging which can also present with amyloid plaques and whose Aβ is highly homologous to humans’. In an attempt to characterize this primate model and to evaluate the potential of plasma Aβ as a biomarker for brain alterations, we measured plasma Aβ40 concentration in 21 animals aged from 5 to 9.5 years. We observed an age-related increase in plasma Aβ40 levels. We then evaluated the relationships between plasma Aβ40 levels and cerebral atrophy in these mouse lemurs. Voxel-based analysis of cerebral MR images (adjusted for the age/sex/brain size of the animals), showed that low Aβ40 levels are associated with atrophy of several white matter and subcortical brain regions. These results suggest that low Aβ40 levels in middle-aged/old animals are associated with brain deterioration. One special feature of mouse lemurs is that their metabolic and physiological parameters follow seasonal changes strictly controlled by illumination. We evaluated seasonal-related variations of plasma Aβ40 levels and found a strong effect, with higher plasma Aβ40 concentrations in winter conditions compared to summer. This question of seasonal modulation of Aβ plasma levels should be addressed in clinical studies. We also focused on the amplitude of the difference between plasma Aβ40 levels during the two seasons and found that this amplitude increases with age. Possible mechanisms leading to these seasonal changes are discussed.